Estudo químico e atividade larvicida do óleo essencial das folhas de Piper aduncum L. - Figueiredo, Pablo Busatto (2014)
Essential oils produced by various plant species are mixtures sometimes quite complex with varied ecological functions, such as inhibition of germination, protection against predators, attraction of pollinators, protection against water loss and temperature rise. Essential oils are obtained by physical extraction methods and present several applications, such as flavorings, preservatives, fixatives, antibacterial and antifungal agents. Various industrial products also use essential oils in their formulations, such as pesticide repellents and attractive presenting as a natural alternative to control or eliminate pests. The restriction of some synthetic pesticides further promoted the search for new products that could play the role of those who are no longer available in the market. Several biopesticides are reported and among them dilapiolle, which is a phenylpropanoid with proven insecticidal activity found in high content in essential oil of Piper aduncum L. (Piperaceae). In this work, we analyzed the quantitative variability in dilapiolle essential oils (EO) obtained from fresh leaves of P. aduncum and when subjected to 24, 48, 72 and 96 h of drying at 40 °C. The EO underwent hydrogenation and hydroxylation reactions in search of more active biopesticides and all products were analyzed by GC-MS, NMR 1H and NMR 13C. The content of dilapiolle was analyzed by GC-FID and HPLC, yielding on average 89.68 % and 89.91 % respectively and showed that the drying temperature does not influence the content of this compound in P. aduncum EO. The second major component of the oil was identified as β-caryophyllene (4.47 %). The test larvicide against Aedes aegypti performed provided IC50 of 47.12 mg/L, confirming the potential of this product as a biopesticide.